Interleukin-1 receptor associated kinase 1 (IRAK1) is epigenetically activated in luminal epithelial cells in prostate cancer - Schagdarsurengin, Undraga; Breiding, Vanessa; Loose, Maria; Wagenlehner, Florian; Dansranjav, Temuujin (Frontiers in Oncology, 2022)
The use of immune adjuvants such as toll-like receptor (TLR) agonists reflects a novel strategy in prostate cancer (PCa) therapy. However, interleukin-1 receptor associated kinase 1 (IRAK1), a central effector of TLR signaling, has been shown to be responsible for resistance to radiation-induced tumor cell death. In order to better understand the function and epigenetic regulation of IRAK1 in PCa, we performed in vitro cell culture experiments together with integrative bioinformatic studies using the latest single-cell RNA-sequencing data of human PCa and normal prostate (NOR), and data from The Cancer Genome Atlas. We focused on key effectors of TLR signaling, the Myddosome-complex components IRAK1, IRAK4 and MYD88 (myeloid differentiation primary response 88), and TRAF6 (tumor-necrosis-factor receptor associated factor 6). In PCa, IRAK1-mRNA was specifically enriched in luminal epithelial cells, representing 57% of all cells, whereas IRAK4 and MYD88 were predominantly expressed in leukocytes, and TRAF6, in endothelial cells. Compared to NOR, only IRAK1 was significantly overexpressed in PCa (Benjamini-Hochberg adjusted p<2x10-8), whereas the expression of IRAK4, MYD88, and TRAF6 was unchanged in PCa, and IRAK1-expression was inversely correlated with a specific differentially methylated region (IRAK1-DMR) within a predicted promoter region enriched for H3K27ac (Spearman correlation r<-0.36; Fisher’s test, p<10-10). Transcription factors with high binding affinities in IRAK1-DMR were significantly enriched for canonical pathways associated with viral infection and carcinogenic transformation in the Kyoto Encyclopedia of Gene and Genomes analysis. DU145 cells, exhibiting hypermethylated IRAK1-DMR and low IRAK1-expression, reacted with 4-fold increased IRAK1-expression upon combined treatment with 5-aza-2-deoxycytidine and trichostatin A, and were unresponsive to infection with the uropathogenic Escherichia coli strain UTI89. In contrast, PC3 and LNCaP cells, exhibiting hypomethylated IRAK1-DMR and high endogenous IRAK1-mRNA levels, responded with strong activation of IRAK1-expression to UTI89 infection. In summary, exclusive overexpression of IRAK1 was observed in luminal epithelial cells in PCa, suggesting it has a role in addition to Myddosome-dependent TLR signaling. Our data show that the endogenous epigenetic status of PCa cells within IRAK1-DMR is decisive for IRAK1 expression and should be considered as a predictive marker when selective IRAK1-targeting therapies are considered.